The Influence of Piano Accompaniment Music on the Psychology and Expressiveness of Sports Dancers - Yuanyuan Han (Revista de Psicología del Deporte (Journal of Sport Psychology), 2024)
As the foundational element of sports dance, music serves as its quintessential "soul," profoundly influencing the artistic allure and evolutionary trajectory of the discipline. Frequently, it unveils the distinctive charisma of sports dance to global audiences through its intricate rhythmic patterns, melodious compositions, and fervent and uninhibited style. Given the imperative of harmoniously integrating sports dance technique with musical artistry to enhance its expressive capacities, this research endeavours to scrutinize the impact of piano accompaniment music on the psychology and expressive dimensions of sports dancers. Experimental findings substantiate the noteworthy influence of piano accompaniment music training on the expressive prowess exhibited by sports dance athletes. This investigation systematically scrutinized the expressive capacity inherent in sports dance art through the lens of music. By methodically analysing pertinent factors encompassing music training and the expressive capabilities inherent in sports dance art, the pivotal role of music training in augmenting the expressive potency of sports dance art was validated. To corroborate this assertion, a pedagogical experiment employing a single-factor comparative analysis was adopted, elucidating the artistic manifestation within sports dance from an empirical vantage point. Following the experimental intervention, the measurement scores of students within the experimental cohort exhibited a statistically significant elevation in comparison to those of the control group (P < 0.05). These outcomes underscore the pronounced impact of music training on the rhythmic acuity and coordination of sports dancers. Moreover, post-experiment performance in sports skills demonstrated a notable enhancement within the experimental cohort relative to the control group (P < 0.05), further affirming the beneficial effects of music training on sports performance. By honing the rhythmic sensibility instilled through dance music, mastering sequences of movements, grasping the intricacies of dance music, and undergoing collaborative training integrating music with choreographed routines, the artistic expression of dance athletes can be significantly enhanced. Facilitating the fusion of artistry and athleticism, policymakers are encouraged to advocate for the amalgamation of art and sports, thereby fostering an environment conducive to the development of sports dance. This entails provisioning of enhanced artistic resources and training opportunities tailored specifically for sports dance athletes, including guidance and collaboration in musical accompaniment. Provision of professional accompaniment teams is recommended, with policymakers contemplating the establishment of dedicated piano accompaniment teams for sports dance athletes to ensure the calibre and adaptability of musical accompaniment, thereby elevating athletes' performance standards.